English Tag Question as Linguo-Ecological Phenomenon of Interpersonal Communication - V. V. Selezneva; E. A. Evsikova; A. Sh. Tarverdyan (Научный диалог)
The article considers the functional properties of English tag questions from the perspective of a relatively new linguistic paradigm - linguistic ecology. The novelty of the research is seen in the fact that up to now these syntactic units have not received proper coverage in the linguo-ecological key. Tag questions in the discursive segments selected from the English corpus of modern fiction and film discourse were the material for the analysis. The authors present a tag question with its pre-defined and discursive meanings as a stereotypical linguistic model, designed to support the harmony of speech communication of representatives of the English linguistic culture. During the discourse analysis the following characteristics of linguoecological compatability of a tag question were highlighted: non-categoricalness, tolerance, addressee centricity, empathy, mitigation. Particular attention is paid to the strategies of communicative defocusing and hedging, adequate operation of which is the key to reducing communication risks and achieving harmonious communication. By examples of various structural and pragmatic types of tag questions, the role of assertive-evaluative, modus, deictic, directive and emotive mitigation is shown in maintaining ecological mode of communication. It is concluded that the basis of tag question ecological functioning is the syncretism of the dominant features of the English communicative style - distancing, indirectness, non-categoricalness, mitigation of directive intentions and emotive de-intensification.